Plasmonic random lasing and amplified spontaneous emission from donor–acceptor–donor dyes covered biocompatible silk fibroin film. Issue 14 (28th March 2023) - Lin, Ja-Hon; Tung, Po-Han; Tsai, Wei-Chen; Setyatama, Novia Eka; Lin, Tzu-Chau; Kuo, Chi-Ching; Lin, Bi-Hsuan; Lin, Hao-Wu; Yeh, Ting-Ju; Wang, Yun-Chi
Abstract : Amplified spontaneous emission and random lasing behavior are demonstrated from our synthesized donor–acceptor–donor dye-covered biocompatible silk fibroin (DC-SF) film and the DC-SF film with embedded silver nanoprisms, respectively. Abstract : The investigation of novel organic laser dye in combination with a high transparency biopolymer film will promote the development of cost-effective organic solid state lasers as a promising tunable coherent light source for applications in bio-diagnosis, medical surgery, and high resolution spectroscopy. Herein, we design and synthesize a series of highly emissive organic chromophores with the generic structure of donor–acceptor–donor (D–A–D), which were directly applied on the surface of a biocompatible silk fibroin (SF) film via a simple solution process to form a dye-covered film for the investigation of their potentiality as organic solid state lasers. Owing to their large gain cross section, the distinct amplified spontaneous emission (ASE) from blue to green has emerged from the surface normal of these dye-covered SF (DC-SF) films depending on the used chromophores. On the other hand, the embedding of silver nanoprisms (AgNPs) into the SF matrix is found to efficiently enlarge the photon localization to generate coherent feedback, which could be attributed to the enhancement of recurrent light scattering and localized surface plasmon resonance. The low threshold plasmonic random laser generated from the aforementioned AgNPs embedded dye-covered SF film ( i.e., DC-SF/AgNPs) has been used to produce the speckle-reduced image with low contrast of around 0.024.